2021
DOI: 10.3847/1538-4357/ac23c6
|View full text |Cite
|
Sign up to set email alerts
|

The Gravity Collective: A Search for the Electromagnetic Counterpart to the Neutron Star–Black Hole Merger GW190814

Abstract: We present optical follow-up imaging obtained with the Katzman Automatic Imaging Telescope, Las Cumbres Observatory Global Telescope Network, Nickel Telescope, Swope Telescope, and Thacher Telescope of the LIGO/Virgo gravitational wave (GW) signal from the neutron star–black hole (NSBH) merger GW190814. We searched the GW190814 localization region (19 deg2 for the 90th percentile best localization), covering a total of 51 deg2 and 94.6% of the two-dimensional localization region. Analyzing the properties of 18… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 178 publications
0
8
0
Order By: Relevance
“…At of the end of O3, several GW detections of NS-BH merger candidates have been reported (Abbott et al 2021;The LIGO Scientific Collaboration et al 2021a), but no EM counterpart to an NS-BH merger was found (e.g., Anand et al 2021;Dichiara et al 2021; for the most robust NS-BH GW detections). Extensive follow-up was also performed for the peculiar source GW190814 (Dobie et al 2019;Gomez et al 2019;Ackley et al 2020;Andreoni et al 2020;Morgan et al 2020;Thakur et al 2020;Vieira et al 2020;Watson et al 2020;Alexander et al 2021;de Wet et al 2021;Kilpatrick et al 2021;Dobie et al 2022;Tucker et al 2022). However, the nature of the secondary component of GW190814 is unclear, as it can be either the lightest black hole or the heaviest NS ever discovered in a double compactobject system (Abbott et al 2020c).…”
Section: The Rubin Quest For the Unknown: Em Counterparts To Ns-bh Me...mentioning
confidence: 99%
See 1 more Smart Citation
“…At of the end of O3, several GW detections of NS-BH merger candidates have been reported (Abbott et al 2021;The LIGO Scientific Collaboration et al 2021a), but no EM counterpart to an NS-BH merger was found (e.g., Anand et al 2021;Dichiara et al 2021; for the most robust NS-BH GW detections). Extensive follow-up was also performed for the peculiar source GW190814 (Dobie et al 2019;Gomez et al 2019;Ackley et al 2020;Andreoni et al 2020;Morgan et al 2020;Thakur et al 2020;Vieira et al 2020;Watson et al 2020;Alexander et al 2021;de Wet et al 2021;Kilpatrick et al 2021;Dobie et al 2022;Tucker et al 2022). However, the nature of the secondary component of GW190814 is unclear, as it can be either the lightest black hole or the heaviest NS ever discovered in a double compactobject system (Abbott et al 2020c).…”
Section: The Rubin Quest For the Unknown: Em Counterparts To Ns-bh Me...mentioning
confidence: 99%
“…The third Advanced LIGO, Virgo, and KAGRA (LVK) observing run (O3, which ran in 2019-2020) yielded the solid detection of the second binary neutron star (NS-NS) merger (GW190425; Abbott et al 2020a), at least two neutron star-black hole (NS-BH) mergers (GW200105 and GW200115; Abbott et al 2021), and several other NS-NS or NS-BH candidates (The LIGO Scientific Collaboration et al 2021a). Despite much follow-up effort, no EM counterpart was identified during O3 in the optical (e.g., Andreoni et al 2019bAndreoni et al , 2020Coughlin et al 2019a;Goldstein et al 2019;Gomez et al 2019;Hosseinzadeh et al 2019;Lundquist et al 2019;Ackley et al 2020;Antier et al 2020;Garcia et al 2020;Gompertz et al 2020;Kasliwal et al 2020;Vieira et al 2020;Anand et al 2021;Becerra et al 2021;Chang et al 2021;Kilpatrick et al 2021;Oates et al 2021), in the radio (Dobie et al 2019;Alexander et al 2021;Bhakta et al 2021), or during X-ray/high-energy observations (Page et al 2020;Watson et al 2020;see, however, Pozanenko et al 2020). The task was made particularly difficult by the coarse localization regions (median localization area of 4480 deg 2 ; Kasliwal et al 2020) and large distances (median distance of 267 Mpc; Kasliwal et al 2020) of NS-NS and NS-BH merger candidates (see also The LIGO Scientific Collaboration et al 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Photometry is performed by one of two different general methods depending on the specifics of the field in question and the scientific requirements. While our pipeline is evolving and is subject to change, we outline the basic features of each method as our data has been used in published scientific works including the monitoring of Boyajian's Star (Boyajian et al 2018;Wilcox et al 2019) and Boyajian Star analogs (Arculli et al 2020;Browning et al 2021), eclipsing binaries (Healy et al 2019), transiting exoplanets (Jin-Ngo et al 2021), and transient studies (Swift et al 2018(Swift et al , 2019Jacobson-Galán et al 2020;Barna et al 2021;Gagliano et al 2022;Kilpatrick et al 2021;Sand et al 2021;Tinyanont et al 2021).…”
Section: Data Reduction and Analysismentioning
confidence: 99%
“…The third LIGO/Virgo/KAGRA (LVK) collaboration observing run (O3) resulted in over 60 new events (see the third Gravitational-wave Transient Catalog, GWTC; LIGO Scientific Collaboration et al 2023). One GW event originated from a BNS merger, and two high-confidence events originated from NS-BH coalescences (Abbott et al 2021), but no EM counterparts were confirmed from any event despite extensive follow-up campaigns (e.g., Andreoni et al 2019Andreoni et al , 2020Goldstein et al 2019;Garcia et al 2020;Morgan et al 2020;Kilpatrick et al 2021;Oates et al 2021;Tucker et al 2022). One study (Graham et al 2020) proposed an AGN counterpart to the binary black hole merger GW190521, but the association with the GW event cannot be made with confidence (Ashton et al 2021;Palmese et al 2021b).…”
Section: Introductionmentioning
confidence: 99%